The process of MA-XRF data for spectroscopy imaging in cultural heritage - Huseynli, Fakhriyya (2021)
Scanning macro-X-ray fluorescence analysis (MA-XRF) is rapidly being established as a technique for the investigation of historical paintings. The elemental distribution images acquired by this method allow the visualization of hidden paint layers and thus, provide insight into the artist's creative process and the painting's conservation history. As a non-destructive instrument MA-XRF and analyzing software PyMca will be used to identify, also to study painting from private collection in Italy. The use of MA-XRF to tentatively predict pigments has an important advantage, its application provides the undamaged and low cost survey of large areas in the painting. The method was proved powerful and useful, capable of efficiently determining the composition and structure of the investigated object in a total safe approach. Nevertheless, for a more throughout evaluation and a better estimation of the pigment composition, it has been demonstrated that, the use of complementary analytical techniques is required